The Psychological Impact of COVID-19 Disease is more Severe on Intensive Care Unit Healthcare Providers: A Cross-sectional Study - SARAÇOĞLU, AYTEN (KOREAN COLL NEUROPSYCHOPHARMACOLOGY, 2020)
Objective: Fear, anxiety, depression and sleep deprivation are common mental health disorders in COVID-19 disease. We aimed to analyse the risk for healthcare providers during COVID-19 pandemic in a university hospital. Methods: Anesthesiologists, nurses and nurse anesthetists were invited to fill out the survey. The survey was consist of questions from The Fear of COVID-19 Scale, Patient Health Questionnaire and Pittsburgh Sleep Quality Index (PSQI). Each question was worth a point. Results: The data of 208 participants were analyzed. Mean age was 29 +/- 7.748 years, 72.1% were male, 67.3% were nurses, 62% were working in intensive care units, 38% were in hospital wards, 62% of all participants were living alone. Moderate depression was the most frequently detected outcome (n = 90, 43.3%). Mean The Fear of COVID-19 Scale for all participants was 18.56 +/- 7.731. The mean PSQI of patients was 6.18 +/- 4.356 with a 45.7% rate of poor sleep quality. PSQI was found significantly higher in nurses (7.1 +/- 4.7, p = 0.000). Nurses were the group with the highest deterioration in sleep quality (53.6%, p = 0.003). The rate of moderate-to-severe depressive symptoms was significantly higher in intensive care unit nurses and physicians (p = 0.018). PSQI score was found significantly higher in intensive care unit nurses and physicians than hospital ward co-workers (7.02 +/- 4.59 vs. 4.81 +/- 3.57 respectively, p = 0.001). A significant positive correlation was observed between PSQI and The Fear of COVID-19 Scale total score in all patients (p < 0.005). Conclusion: Depression, anxiety, fear and sleep disorders may occur in healthcare workers during COVID-19 outbreak. Intensive care unit nurses were at highest risk.
Keywords: COVID-19; Mental health; Intensive care unit; Pandemic; SLEEP QUALITY INDEX; RISK; SARS